2015
DOI: 10.1007/s10064-015-0753-6
|View full text |Cite
|
Sign up to set email alerts
|

Stability assessment of high-steep cut slope debris on a landslide (Gumushane, NE Turkey)

Abstract: The objective of this study was to examine the effects on the stability of slope debris of planned slope excavations around the vicinity of Gumushane Imam-Hatip High School in NE Turkey. To assess the geotechnical properties of slope debris along the determined cross-sections, four exploration boreholes with a total length of 100 m were drilled and undisturbed soil samples were collected. Slope debris is composed of two soil zones and its depth varies between 15 m and 21 m. It was determined from the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 32 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…The physical properties of soil are the internal factors leading to soil erosion, the degree of soil erosion is usually related to the physical properties of soil itself under certain external forces (Kaya et al, 2016). The above research showed that the soil of timber forest and shrubby grassland could absorb nutrients and reduce soil erosion out of better soil structure; under the same rainfall conditions, the loss of terraced soil in runoff and sediment were all lower than sloping farmland while the concentration of TN and TP were higher than that of other soil, which fully indicated that terrace could store and collect nutrients and achieve on-site infiltration of rainwater.…”
Section: Discussionmentioning
confidence: 99%
“…The physical properties of soil are the internal factors leading to soil erosion, the degree of soil erosion is usually related to the physical properties of soil itself under certain external forces (Kaya et al, 2016). The above research showed that the soil of timber forest and shrubby grassland could absorb nutrients and reduce soil erosion out of better soil structure; under the same rainfall conditions, the loss of terraced soil in runoff and sediment were all lower than sloping farmland while the concentration of TN and TP were higher than that of other soil, which fully indicated that terrace could store and collect nutrients and achieve on-site infiltration of rainwater.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, a certain section of the road can function as a barrier, a network resource, a network pool, or a corridor for water flow [91][92][93]. It can indirectly cause landslides by increasing the water concentration in the slope, including saturated slopes [11,30]. Another crucial point is the change of natural hydraulic roads that may water to concentrate in the imbalanced sections of the slope [27].…”
Section: The Effect Of the Road Distance Parameter On Landslidesmentioning
confidence: 99%
“…Due to the weathering effect of the drainage, it drags the materials from the toe point and eventually causes stepped landslides that trigger movements from the toe to the top elevation with lateral spreading [131]. Pore water pressure is affected, which affects susceptibility [30]. Timilsina et al [44], in his works, considers the closeness to certain drainages as it applies.…”
Section: Effects Of Distance To Drainage Parameters On Landslidementioning
confidence: 99%
See 2 more Smart Citations